Longitudinal follow up study of clinical and anthropometric profile of severely malnourished children admitted at nutrition rehabilitation centre - Makavana, Jignesh; Tallikoti, Akash; Tollawala, Pinakini; Patel, Ankur; Suthar, Kriti (International Journal of Contemporary Pediatrics, 2025)
Background: Nutritional status of children is the common factor to identify the nutritional status of the entire community. Hence, this study was designed to look for clinical and anthropometric profiles of severely malnourished children during admission, discharge and follow up of the child admitted at nutrition rehabilitation centre (NRC) of our hospital. Methods: Patients will be monitored and outcome will be seen in the form of vital and clinical parameters and detailed anthropometric assessment at admission, discharge and follow up. Total 3 follow up will be done at an interval of 15 days as per MOHFW operational guideline. Results: Females (n=42, 56%) were slightly more as compared to males (n=33, 44%). Statistically significant results were found with respect to increase in the mean MUAC among subjects from discharge to 3rd follow-up. At discharge mean weight of the subject was 7.38 which increased to 8.99 after 3rd follow-up. When weight was compared with different time interval using ANOVA test; statistically significant result was found as p=0.002. At admission mean height of the subject was 74.73, after 3rd follow-up increased up to mean of 81.02, this shows from the discharge to 3rd follow-up as per time height of the subjects was increasing. When height was compared according to different time interval using ANOVA test; statistically significant result was found. Conclusions: NRCs provide life-saving care for complicated severe acute malnutrition (SAM) children with high chances of recovery rate in clinical and anthropometric parameter. Follow up visits are more important for clinical and anthropometric assessment of child and counselling of parent. Large number of uncomplicated SAM child can be treated in their community with traditionally available energy dense food.